Advertising and values through time as social influence - Ballesteros-Ocampo, Nayibe
This article presents a literature review that discusses how advertising and brands have adapted to generational changes by incorporating ethical and moral values, thereby transforming their language to communicate with new audiences, specifically Centennials. Through an exploration of this generation and a general review of past ones, their social contexts, motivations, and ethical and moral values are analyzed. The aim is to understand the influence of these values on current advertising targeted at this specific group of young people, born between 1997 and 2006, who have grown up in the digital age, surrounded by technology and social media.